New insight on designing docetaxel prodrug liposomes with high stability and intelligent release: Length-like or structure-like modification strategy - Si Zheng; Danping Wang; Zhiyu Kuang; Shengyao Xu; Wenxiao Li; Haiyu Zhao; Jingyi Zhang; Weiyao Li; Zhonggui He; Jin Sun; Lin Li; Bingjun Sun (Chemical Engineering Journal, 2026)

The dual role of intestinal bacteria in the colorectal cancer treatment: From pathogenic risk to new therapeutic strategies - Shuo Wang; Wenjing Wang; Yuhang Zhang; Yaqi Li; Qi Zhang; Jun Yuan; Tian Liu; Jin Sun; Xiwei Jiang; Bingjun Sun (Chemical Engineering Journal, 2026)

Enantioselective migration, degradation, and metabolism of pyriproxyfen and its metabolites from tea garden to cup - Hongxia Li; Yue Hu; Yating Ning; Qing Zhong; Hezhi Sun; Xinru Wang; Mei Yang; Fengjian Luo; Li Zhou; Bingjun Han; Xinzhong Zhang (Food Chemistry, 2026)

Insights into the effects of different nitrogen sources on microbial metabolic function and biodegradation of bituminous coal - Yundu Yang; Bingjun Liu; Sheng Xue; Junyu Wang; Xiangqing Jiang; Ruifeng Chen; Rui Sun; Keyang Cheng (Fuel, 2026)

Decoding iodine chemisorption confinement by a PEI-graphene host in aqueous Zn-I₂ batteries via scanning electrochemical microscopy - Lei Liu; Ni Zhang; Hang Liu; Minghui Xue; Bingjun Yang; Juan Yang; Dongfei Sun (Chemical Engineering Journal, 2026)

Research on High Prestress Rock Bolt Support Mechanism for Jointed Surrounding Rock in Tunnels Through Structural Plane Stress Compensation Analysis - Weiteng Li; Guanghui Yang; Bingjun Sun; Yuchun Mei; Xianfeng Yin; Yang Li; Shujun Jiao; Tingchun Li (Rock Mechanics and Rock Engineering, 2026)

Programmable manganese-chalcogen coordination nanoregulator enables dual-lock prodrug activation through electron cloud engineering for synergistic chemo-metalloimmunotherapy - Jingzhe Sheng; Tengda Du; Jingyi Zhang; Yuetong Huang; Shuo Wang; Mengyu Liu; Tao Zhang; YingJie Zhao; Hao Zhang; Qian Lv; Can Zhao; Xiaoxue He; et al. (Chemical Engineering Journal, 2025)

Exploring the interaction between vermicompost application and soil types on the dispersal of antibiotic resistome above- and belowground - Meirui Mu; Keqiang Zhang; Ming Yang; Bingjun Han; Yutao Sun; Fengxia Yang (Applied Soil Ecology, 2025)

Branched fatty acids in prodrug nanoassemblies: Molecular gating for governing stability and activation efficiency to amplify therapeutic benefits - Yongke Zhang; Zuo Zhang; Baoyuan Zhang; Dongyu Zhang; Wenfeng Zang; Siyun Zheng; Yiming Lu; Jin Sun; Bingjun Sun; Zhonggui He; Yixin Sun (Chemical Engineering Journal, 2025)

A fatty acid modification strategy to improve the binding affinity of Epirubicin to human serum albumin for efficient cancer therapy - Minglong Huang; Xin Wang; Jialin Xing; Bowen Zhang; Lurong Zhang; Yaqiao Li; Hongying Xiao; Qing Wang; Jun Yuan; Yafan Xiao; Zhenzhen Zhao; Zhonggui He; et al. (Chemical Engineering Journal, 2025)

Optimizing the stable doxorubicin prodrug nanocomplex for efficient and selective cancer therapy - Hongying Xiao; Jinrui Liu; Minglong Huang; Wenfeng Zang; Bowen Zhang; Shufang Zheng; Xin Li; Zhonggui He; Xin Wang; Huaiwei Ding; Lingxiao Li; Bingjun Sun (Chemical Engineering Journal, 2025)

Evaluation of forage quality in various soybean varieties and high-yield cultivation techniques - Baiquan Sun; Shan Yuan; Mahmoud Naser; Yanfeng Zhou; Hongchang Jia; Yang Yu; Xiangyu Yao; Tingting Wu; Wenwen Song; Bingjun Jiang; Hongxia Dong; Chunlei Zhang; et al. (Field Crops Research, 2024)

Reductants supplement boost the antitumor efficacy of nanomedicine - Zhiyu Kuang; Danping Wang; Qing Wang; Shengyao Xu; Hezhen Xu; Shiyi Zuo; Yaqiao Li; Hao Zhang; Cuiyun Liu; Xiaohui Pu; Jin Sun; Yuezhou Zhang; et al. (Chemical Engineering Journal, 2024)

Analysis of extracellular and intracellular antibiotic resistance genes in commercial organic fertilizers reveals a non-negligible risk posed by extracellular genes - Ran Zhao; Bingjun Han; Fengxia Yang; Zulin Zhang; Yutao Sun; Xue Li; Yiming Liu; Yongzhen Ding (Journal of Environmental Management, 2024)

Hybrid nanoassembly indicating a synthetic lethality relationship induces mitotic catastrophe-mediated tumor elimination - Shunzhe Zheng; Guanting Li; Shuwen Fu; Nannan Wang; Han Qiao; Meng Li; Xuanbo Zhang; Kaiyuan Wang; Wei Sun; Chutong Tian; Zhonggui He; Defang Ouyang; et al. (Chemical Engineering Journal, 2024)

Ice-Induced Vibration Analysis of Offshore Platform Structures Based on Cohesive Element Method - Jianhua Zhang; Xiaoyu Wang; Ke Sun; Yueqi Lai; Dianwei Gao; Won-Hee Kang; Bin Wang; Bingjun Wang (Journal of Marine Science and Engineering, 2023)
This study conducted ice-induced vibration analysis on offshore platform structures using the cohesive element method (CEM). The efficacy of this method in simulating the interaction between sea ice and the platform structure is verified by comparing it with the Hamburg Ship Modeling Pool (HSVA) ice-breaking experiment. Subsequently, the vibration response of a sea-ice-jacket platform model is investigated under both unprotected conditions and with the presence of ice-breaking cones. The findings reveal that the motion response of offshore platforms exhibits a positive correlation with the impact velocity of the ice, while the sensitivity of this impact is found to be minimal. Furthermore, the influence of different ice directions on the vibration response of offshore platforms is significant, and the shielding effect has an important impact on the platform’s response. Notably, offshore platforms equipped with 52.5-degree cones demonstrate the most effective vibration reduction, reducing the maximum acceleration by 63% compared to unprotected configurations. It is worth mentioning that as the cone angle increases, the corresponding ice-breaking cone undergoes higher load-bearing.

Genome-wide association study for temperature response and photo-thermal interaction of flowering time in soybean using a panel of cultivars with diverse maturity groups - Tingting Wu; Huiwen Wen; Xinyue Zhang; Hongchang Jia; Cailong Xu; Wenwen Song; Bingjun Jiang; Shan Yuan; Shi Sun; Cunxiang Wu; Tianfu Han (Theoretical and Applied Genetics, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Influence of transition metal catalysts on the decomposition product distribution of PCBs and PCDD/Fs - Xingshuang Liu; Bingjun Zhu; Qiqi Wang; Congcong Zhang; Ye Wang; Yifei Sun (Science of The Total Environment, 2023)

Geographic distributions and the regionalization of soybean seed compositions across China - Wenwen Song; Shi Sun; Tingting Wu; Ruping Yang; Shiyan Tian; Cailong Xu; Bingjun Jiang; Shan Yuan; Wensheng Hou; Cunxiang Wu; Tianfu Han (Food Research International, 2023)

Rational design of tumor-selective prodrug nanoassemblies: Greatly improving the in vivo fate and tolerability of high-toxic cabazitaxel - Jingxuan Zhang; Yu Zhang; Yuetong Huang; Danping Wang; Shiyi Zuo; Hezhen Xu; Zhonggui He; Qiming Kan; Xiaohong Liu; Bingjun Sun; Jin Sun (Chemical Engineering Journal, 2023)

Transcriptome Profile of a Long-Juvenile Soybean Genotype Huaxia-3 Under Short and Long Photoperiod - Enoch Sapey; Bingjun Jiang; Luping Liu; Shan Yuan; Tingting Wu; Seifeldin Elrayah Ibrahim; Shi Sun; Yanlei Yue; Tianfu Han (Plant Molecular Biology Reporter, 2022)
The j allele delays flowering and enhances yield of long juvenile (LJ) soybean under short day (SD) condition. However, the underlying mechanism of j in flowering pathway of soybean is not fully known. The objective of the study is to profile the transcriptome of Huaxia-3 (HX3), a typical long juvenile soybean variety with a loss of function allele ( j ) for the J gene. This helps to identify the genes implicated in delayed flowering in the long juvenile soybean variety and the pathways involved. Phenotypic analysis revealed HX3-delayed flowering and matured later than the transgenic line with the functional J gene under SD. RNA-Seq analysis was conducted to compare the transcriptome of HX3 relative to the one overexpressing J gene under SD and long day (LD). A total of 674,800,494 clean reads were generated, of which 626,517,161 (93%) were uniquely mapped to the soybean reference genome. A total of 31 and 2311 genes were differentially expressed in the HX3 under SD and LD conditions respectively. The circadian rhythm pathway was the most significantly enriched pathway in the HX3 under SD condition. The GmELF3a ( Glyma.04G050200 ) and FLOWERING LOCUS T ( FT ) genes such as GmFT2a ( Glyma.16G150700 ) and GmFT5a ( Glyma.16G044100 ) were downregulated, whiles GmFT4 ( Glyma.08G363100 ) was upregulated in the HX3 under SD. Under LD FT homologs, GmFT4 ( Glyma.08G363100 ) was downregulated and GmFT1a ( Glyma.18G299000 ) was upregulated. Our study suggests that these FT homologs may be involved in delayed flowering of LJ soybean under SD.

GmFULa improves soybean yield by enhancing carbon assimilation without altering flowering time or maturity - Yanlei Yue; Shi Sun; Jiawen Li; Haidong Yu; Hongxia Wu; Baiquan Sun; Tao Li; Tianfu Han; Bingjun Jiang (Plant Cell Reports, 2021)
Key message GmFULa improved soybean yield by enhancing carbon assimilation. Meanwhile, different from known yield-related genes, it did not alter flowering time or maturity. Abstract Soybean ( Glycine max (L.) Merr.) is highly demanded by a continuously growing human population. However, increasing soybean yield is a major challenge. FRUITFULL ( FUL ), a MADS-box transcription factor, plays important roles in multiple developmental processes, especially fruit and pod development, which are crucial for soybean yield formation. However, the functions of its homologs in soybean are not clear. Here, through haplotype analysis, we found that one haplotype of the soybean homolog GmFULa ( GmFULa-H02 ) is dominant in cultivated soybeans, suggesting that GmFULa-H02 was highly selected during domestication and varietal improvement of soybean. Interestingly, transgenic overexpression of GmFULa enhanced vegetative growth with more biomass accumulated and ultimately increased the yield but without affecting the plant height or changing the flowering time and maturity, indicating that it enhances the efficiency of dry matter accumulation. It also promoted the yield factors like branch number, pod number and 100-seed weight, which ultimately increased the yield. It increased the palisade tissue cell number and the chlorophyll content to promote photosynthesis and increase the soluble sugar content in leaves and fresh seeds. Furthermore, GmFULa were found to be sublocalized in the nucleus and positively regulate sucrose synthases ( SUSs ) and sucrose transporters ( SUTs ) by binding with the conserved CArG boxes in their promoters. Overall, these results showed GmFULa promotes the capacity of assimilation and the transport of the resultant assimilates to increase yield, and provided insights into the link between GmFULa and sucrose synthesis with transport-related molecular pathways that control seed yield.

Tissue distribution and dermal drug determination of indomethacin transdermal-absorption patches - Jingjing Ma; Ying Gao; Yinghua Sun; Dawei Ding; Qi Zhang; Bingjun Sun; Menglin Wang; Jin Sun; Zhonggui He (Drug Delivery and Translational Research, 2017)

Erratum to: The role of particle size of glyburide crystals in improving its oral absorption - Wenqian Yang; Yongjun Wang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)

The role of particle size of glyburide crystals in improving its oral absorption - Yongjun Wang; Wenqian Yang; Qiang Fu; Zhibin Guo; Bingjun Sun; Wen Liu; Yaxuan Liu; Simeng Mu; Mengran Guo; Jingru Li; Xiaohui Pu; Zhonggui He (Drug Delivery and Translational Research, 2017)

Rapid repair techniques for severely earthquake-damaged circular bridge piers with flexural failure mode - Zhiguo Sun; Hongnan Li; Kaiming Bi; Bingjun Si; Dongsheng Wang (Earthquake Engineering and Engineering Vibration, 2017)

Experimental and numerical investigations on the seismic behavior of bridge piers with vertical unbonded prestressing strands - Zhiguo Sun; Dongsheng Wang; Kaiming Bi; Bingjun Si (Bulletin of Earthquake Engineering, 2016)

The characterization of GmTIP, a root-specific gene from soybean, and the expression analysis of its promoter - Li Chen; Bingjun Jiang; Cunxiang Wu; Shi Sun; Wensheng Hou; Tianfu Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

GmFULa, a FRUITFULL homolog, functions in the flowering and maturation of soybean - Zhen Jia; Bingjun Jiang; Xiaowei Gao; Yanlei Yue; Zhihong Fei; Hongbo Sun; Cunxiang Wu; Shi Sun; Wensheng Hou; Tianfu Han (Plant Cell Reports, 2015)

Rapid repair of severely earthquake-damaged bridge piers with flexural-shear failure mode - Zhiguo Sun; Dongsheng Wang; Xiuli Du; Bingjun Si (Earthquake Engineering and Engineering Vibration, 2011)

Experimental research and finite element analysis of bridge piers failed in flexure-shear modes - Zhiguo Sun; Bingjun Si; Dongsheng Wang; Xun Guo (Earthquake Engineering and Engineering Vibration, 2008)